Educação cristã na igreja em células: análise crítica da concepção de ensino no modelo de treinamento do Ministério Igreja em células no Brasil - Silva Filho, Osvaldo Cipriano da (2010)
The present research aim to analyze the conception of teaching of the Cell Church, according to Ralph W. Neighbour Jr. s model, used by the Cell Church Ministry in Brazil, under the perspective of the continuous Christian education in conformity to the faith of the Reformed Church. The understanding of the Cell Church is that the structure and values of the traditional church do not observe the church model of the New Testament. In a new leather bottle the education lost its significance and the teaching, in its pedagogic conception, returned to the study cycles and training, named trails and weekends , to the formation of leaders and disciple makers, concentrating the forces on the multiplication of the cell and in the growth of the church. In this environment, the biblical school lost its significance and the continuous education on faith was uncharacterized. The member became just a self reproducer. In this study the method of bibliographical research has been chosen starting from the reading of the main works on the subject, emphasizing the exploration of existent sources on the content. The present study is structured in four parts. The first part approaches widely the Christian education starting from the Protestant Reform, highlighting the general historical aspects of the Christian formation of the Presbyterian Church of Brazil. The second part walks through the concept of Christian education and the theoretical aspects of the Four Pillars of Education. Such theoretical conceptions join to the pedagogic proposal of Christian education of the Presbyterian Church of Brazil as identity of Calvinist school starting from its evangelical foundation. As too approaches the biblical school as pedagogic praxis of Christian formation in the traditional church, featuring the Presbyterian Church and the education as Church Ministry. The third part analyzes the pedagogic conception adopted by the cell church according the Christian education ideated by Neighbour Jr. and used by the Cell Church Ministry in Brazil. The research starts from the Cell Church formation and ecclesiological and theological presuppositions. The fourth and last part the study analyzes the formation praxis of training and disciple makers trails by the Cell Church. The last part also presents the characteristics and critics of this research and the proposal of pedagogic model of continuous Christian education on faith for traditional churches which decide to migrate to the cell church model whose conception privileges the disciple makers and leaders formation. The present study concludes that the pedagogic praxis of the cell church is not an instrument of continuous and integral Christian education on faith. It does not seek to treat the individual and prepare him or her for living and it acts in the deconstruction of the biblical school.